Social and environmental determinants of health among children with long-term movement impairment - Hollin, Ilene L.; Bonilla, Bethney; Bagley, Anita; Tucker, Carole A. (Frontiers in Rehabilitation Sciences, 2022)
The healthcare research community increasingly recognizes the need to address social and environmental determinants of health to optimize health and healthcare. This is particularly relevant to disability and functioning, and to those with child onset conditions that impair mobility and impact functioning and participation. Using the World Health Organization (WHO)'s International Classification of Functioning, Disability, and Health (ICF) as a comprehensive framework, this paper aims to discuss our understanding of the relationships between social and environmental determinants of health and outcomes among people with impaired mobility that impacts functioning. This paper offers suggestions for future developments and guidance to use social and environmental determinants of health in research and clinical practice.